Yrjö Kilpinen: Finnish Composer and German Lieder in the 1930s - Deaville, James (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2005)
The Lieder of Finnish composer Yrjö Kilpinen (1892-1959) provide an interesting opportunity to study the interaction of national identity and musical aesthetics in National Socialist Germany. His German-language songs, above all to texts by Christian Morgenstern, enjoyed considerable success in Germany of the 1930s. Kilpinen's own political sympathies made him a model for Nazi ideologists, even as a non-German composing in the quintessentially German musical genre of the Lied. Reviews of his Lieder in the German-language press expound on the "Nordic" qualities of the work of this "Aryan" composer. Closer examination of the Lieder urn den Tod reveals a stark, at times heavy-handed compositional technique, which well suited the political ideology of the Third Reich.